Implementation of Library Automation Based on Senayan Library Management System (SliMS) 9 Bulian - Puteri, Rafa Nabila; Arwan; Kanada, Rabial (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the implementation of library automation based on Senayan Library Management System (SLiMS) 9 Bulian at SMA Negeri 1 Palembang and identify supporting and inhibiting factors in its implementation. The research uses a qualitative approach with a descriptive design to gain an in-depth understanding of the process of implementing the library automation system in the school environment. The research subjects include school principals, library heads, librarians, and students as users. Data collection techniques are carried out through in-depth interviews, observations, and documentation studies, while data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of SLiMS 9 Bulian has included various main library services such as bibliography management, membership management, circulation services, statistical reporting, and collection inventory through the stock taking feature. The implementation of this system is able to improve the efficiency and accuracy of data management, speed up the circulation service process, and make it easier for users to browse collections through the Online Public Access Catalog (OPAC) facility. In addition to having a positive impact on the effectiveness of library services, the implementation of this system also faces several obstacles, such as the limitation of human resources who have information technology competencies and the need for continuous system maintenance. Therefore, school management support, improving librarian competence, and optimizing the use of technology are important factors in the successful implementation of SLiMS-based library automation in the school environment.